Performance and participation in operations of the internal education quality assurance assessment for operational excellence - Wangna, Pensiri; Phantha, Nitaya; Piyakul, Araya (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The study aims to examine the performance and involvement in operations of the internal education quality assurance evaluation for operational excellence (EdPEx) standards. This research employed 36 samples through purposive sampling which consisted of executives, department heads, course chairs, and education faculty heads. Data were acquired through a questionnaire and evaluated using the mean and standard deviation. Findings revealed that performance and involvement in internal education quality assurance evaluation for operational excellence (EdPEx) had a minimal score. For operational excellence, attend training and engage in internal education quality assurance evaluation operations. However, cooperation was significant, particularly to accept faculty and university rules and directives. All 7 areas of internal education quality assurance evaluation for operational excellence challenges and impediments showed moderate problems.